EFFECT OF LIQUIDITY, DIVIDEND POLICY, SALES GROWTH ON COMPANY VALUE - Amar, Abu; Rizal, Noviansyah; Sholihin, Muhammad Rijalus (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to determine whether liquidity, dividend policy, sales growth have an effect on firm value in manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange in 2017-2019. The data collection technique used is porposive sampling so that a sample of 15 companies is obtained. The analytical method used is descriptive analysis, analysis linear regression, classical assumption test and model feasibility test. The results of the study using the partial test (t test) showed that liquidity had a significant positive effect on firm value, dividend policy had a significant positive effect on firm value, and sales growth had a negative effect on firm value. This research method uses quantitative research which is a research method that examines the population or sample, collects data using research instruments, analyzes quantitative data and all of that will be used to test the established hypothesis.